Social learning of the Kichwa language in the family - Ramírez Eras, Angel Marcelo (2024)
Many language learning theories have been designed to develop language skills in any language. This article analyzes the learning of the Kichwa language in the family, particularly in migrant families living in the city of Quito, the capital of Ecuador. For this, the research is based on what is understood by bilingualism, in addition, a survey is applied to a certain group of parents and it is concluded that the family is important for the social learning of the Kichwa language.